Pengaruh Pemberian Vaksin Whole Cell Killed Virus Terhadap Sintasan Udang Vannamei (Lithopenaeus vannamei) Yang Diinfeksi Whitespot Baculovirus (WSBV) [The Influence Of Whitespot Baculovirus (WSBV) Infection In Lithopenaeus vannamei By Giving Whole Cell Killed Virus Vaccine On Survival Rate.] - Hari Suprapto; Angga Bahtera Siswanto; Boedi Setya Rahardja (Jurnal Ilmiah Perikanan dan Kelautan, 2010)
AbstractShrimp are susceptible to a wide variety of pathogens, one of each were viruses. Whitespot Baculovirus (WSBV) is one of virus attack in vannamei. Shrimp had been infected by WSBV will showed high mortality. One of Strategies for prophylaxis and control of WSBV is enhancement of disease resistant by using vaccines. Recently, quasi-immune response have been reported by which Penaeus japonicus surviving from WSBV infections possess a resistance against challenge WSBV (Venegas et al., 2000). This study was used Lithopenaeus vannamei that been vaccination with inactived-formaline WSBV virus cell or it called Whole Cell Killed Virus (WCKV) to know its responses to WSBV. The aim of this study was to know the effect Whole Cell Killed Virus vaccine to survival rate vannamei shrimp (Lithopenaeus vannamei) infected by Whitespot Baculovirus (WSBV). This study used descriptive study. The efficacy of vaccines made of inactivated WSSV with different dose. The dose are P1 (dose 0,01µg/ml each shrimp), P2 (dose 0,02 µg/ml each shrimp), P3 (dose 0,03 µg/ml each shrimp) dan P4 (non-vaccine (kontrol) injected by PBS). Primary parameter was survival rate (%). Secondary parameter was water quality which of temperature, pH, salinity and dissolved oxygen. The result showed that survival rate of L. Vannamei with different dose of WCKV vaccines was increases.